Cereal grain-based functional foods : carbohydrate and phytochemical components - Beta, Trust; Camire, Mary Ellen (Food chemistry, function and analysis, 2019)
Detailed coverage of the composition and functionality of the bulk carbohydrate components and the trace phytochemical components, i.e. phenolic compounds in cereal grains and grain products, is provided for researchers, clinicians and students.